Online Purchasing Trend in the Retail Industry in Saudi - Mohamad Kebah; Valliappan Raju; Zahir Osman (2019)
The concept of online shopping is very popular in the present market scenario. The current trend is indicating the fact that people prefer to shop online because it is easier ad convenient for them. Organizations can easily understand the buying behaviour of the customers by considering different theoretical approaches. The study has indicated that in Saudi Arabia the current trend of online purchasing is at the higher level. People frequently shop online and it is expected that the rate of online shopping in the retail industry in Saudi Arabia will growth further. This study was carried on by using the primary data, which was collected through survey. Survey was conducted with 100 customers in the retail industry in Malaysia. The study used the positivism philosophy for the investigation. The findings in this study are highly important for understanding the latest scenario in the retail industry in Saudi Arabia. The study showed the fact that the people in Saudi Arabia are fond of online shopping. The people are highly motivated for online shopping because of several reasons or benefits that they can enjoy. The findings will be used in the future researches for understanding how the online retail market in Saudi has been developed. This will help to understand the reasons for which the people in this country prefer to shop online. This will also indicate the growth opportunity in the online retailing in Saudi Arabia. The overall findings in this study are highly useful for getting a clear knowledge about the online retailing in Saudi Arabia